2020
DOI: 10.1038/s41467-019-13653-w
|View full text |Cite
|
Sign up to set email alerts
|

Conjunction of triboelectric nanogenerator with induction coils as wireless power sources and self-powered wireless sensors

Abstract: Here we demonstrate a magnetic resonance coupling based wireless triboelectric nanogenerator (TENG) and fully self-powered wireless sensors. By integrating a microswitch and an inductor with the TENG, the pulsed voltage output is converted into a sinusoidal voltage signal with a fixed frequency. This can be transmitted wirelessly from the transmit coil to the resonant-coupled receiver coil with an efficiency of 73% for a 5 cm distance between the two coils (10 cm diameter). Analytic models of the oscillating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 44 publications
0
104
0
Order By: Relevance
“…The harvested energy (0.495 μJ) per cardiac motion cycle was enough to drive the pacemaker (the threshold energy was 0.377 μJ) and realize the self-powered cardiac pacing, which provides a feasible scheme for unattended implantable devices to realize self-powered and sustainable operation. To reduce the energy loss during conversion and storage, Zhang et al 223 demonstrated a wireless power source based on a CS-TENG with a bi-contact micro switch used to reduce the output impedance of the TENG and the inductor coils ( Figure 7D). The microswitch was only closed when the TENG was at the maximum separation or in contact states.…”
Section: Micro/high-voltage Power Sourcesmentioning
confidence: 99%
“…The harvested energy (0.495 μJ) per cardiac motion cycle was enough to drive the pacemaker (the threshold energy was 0.377 μJ) and realize the self-powered cardiac pacing, which provides a feasible scheme for unattended implantable devices to realize self-powered and sustainable operation. To reduce the energy loss during conversion and storage, Zhang et al 223 demonstrated a wireless power source based on a CS-TENG with a bi-contact micro switch used to reduce the output impedance of the TENG and the inductor coils ( Figure 7D). The microswitch was only closed when the TENG was at the maximum separation or in contact states.…”
Section: Micro/high-voltage Power Sourcesmentioning
confidence: 99%
“…(d) Diagram (left) and corresponding circuit (right) of the wireless power transfer network combined with magnetic resonance. Reproduced with permission [90] . Copyright 2020, Springer Nature.…”
Section: Wireless Power Transfer and Information Transmissionmentioning
confidence: 99%
“…The energy could be transferred wirelessly in real time to a length of 60 cm, relying on helical coils. In 2020, Zhang et al [90] demonstrated a wireless TENG based on magnetic resonance coupling, which is shown in Fig. 15d.…”
Section: Wireless Power Transfer and Information Transmissionmentioning
confidence: 99%
“…Combining the low-cost triboelectric sensing mechanism with the large-scale printing technique offers a promising solution. On one hand, triboelectric sensors can produce self-generated electrical signals based on the coupling effect of contact electrification and electrostatic induction [16][17][18][19][20][21] , showing superior merits of simple configuration, great manufacturing compatibility, high scalability, no material limitation, and low cost [22][23][24][25][26][27] . On the other hand, printing techniques such as roll-to-roll printing, inkjet printing, and screen printing have been extensively adopted in large-scale device fabrication [28][29][30][31] .…”
mentioning
confidence: 99%